2023
DOI: 10.2106/jbjs.oa.22.00128
|View full text |Cite
|
Sign up to set email alerts
|

Demographics and Characteristics of Orthopaedic Surgery Residency Program Directors

Abstract: Introduction: To date, there has been a paucity of research evaluating the demographics, characteristics, and surgical training of orthopaedic residency program directors (PDs). Purpose: To determine the objective characteristics of orthopaedic residency PDs by analyzing their demographic characteristics, academic backgrounds, institutional histories, research productivity, and professional leadership affiliations. Methods: Data for each PD were collected by searching publicly available curriculum vitae, Linke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 17 publications
(47 reference statements)
0
6
0
Order By: Relevance
“…Scholarly productivity is one of the quantifiable metrics most often used in determining promotion for academic orthopaedic surgeons. These findings are emphasized in recent studies revealing that women often published fewer articles with overall less impact than men [8, 15, 17]. Similarly, a subsequent study utilized the h-index as a surrogate for academic productivity and noted academic rank increased as mean h-index, m-index, and e-index scores increased [3, 8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Scholarly productivity is one of the quantifiable metrics most often used in determining promotion for academic orthopaedic surgeons. These findings are emphasized in recent studies revealing that women often published fewer articles with overall less impact than men [8, 15, 17]. Similarly, a subsequent study utilized the h-index as a surrogate for academic productivity and noted academic rank increased as mean h-index, m-index, and e-index scores increased [3, 8].…”
Section: Discussionmentioning
confidence: 99%
“…The skewed gender distribution in orthopaedic training programs is likely a function of limited exposure to the field early on, concerns over work-life balance, lack of mentorship, and stereotypes surrounding the specialty [16, 18, 21]. Some have suggested that women in leadership influence gender diversity, serve as role models, and improve recruitment into the specialty [8, 12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be due to factors such as having a larger or more influential network within the institution or the benefit that familiarity with an institution may provide in successfully fulfilling the role of PD ( Van Horne et al ). Some studies have commented on the impact of institutional loyalty on the appointment of PDs across other medical specialties such as cardiothoracic imaging and orthopedic surgery ( Cummings et al, 2023 , Zippi et al, 2022 ) In both of these fields, almost 60% of PDs held positions at institutions where they p.ursued medical education or training ( Cummings et al, 2023 , Zippi et al, 2022 ). This is a higher proportion than our finding for GYO PDs, which may indicate that institutional loyalty plays a more significant role in the appointment of PDs in other fields compared to GYO.…”
Section: Discussionmentioning
confidence: 99%
“…In the 2022 National Residency Match Program (NRMP) survey of program directors, 63% of respondents reported that they seldom or never interview osteopathic applicants while only 16% reported that they seldom or never interview allopathic applicants 8 . This lack of diversity and osteopathic representation is seen throughout the academic spectrum including residents, program directors, and even literature publication rates for orthopaedic journals [9][10][11][12] .…”
Section: Introductionmentioning
confidence: 99%